Crime Prevention through Environmental Design: Discourses of Risk, Social Control, and a Neo-liberal Context - Parnaby, Patrick F. (Canadian journal of criminology and criminal justice, 2006)
This article explores the means by which crime-related risks are discursively framed by practitioners and supporters of Crime Prevention through Environmental Design (CPTED). It will argue that crime-related risks are framed in three interrelated ways: first, as forms of foreseeable danger; second, as depoliticized potentialities; and third, as potentialities that require complete responsibilization. It is argued that these discursive practices constitute the means by which practitioners legitimate their area of professional expertise while at the same time providing them with an opportunity to exercise pastoral control over their client(s). Furthermore, it is argued that these frames demonstrate how "risk" has become an important discourse through which neo-liberal governmentalities (Foucault 1991) with respect to crime control are actualized. (English) [ABSTRACT FROM AUTHOR]